1979
DOI: 10.1029/ja084ia03p00869
|View full text |Cite
|
Sign up to set email alerts
|

Observations of plasma depletion in the magnetosheath at the dayside magnetopause

Abstract: In a set of 17 low-to mid-latitude crossings of the dayside and near-dayside magnetopause, Imp 6 plasma measurements show 11 cases of decreases in magnetosheath density just outside the boundary which are consistent with plasma depletion owing to magnetic flux tube compression as the field becomes draped against the magnetopause. Pressure anisotropies in the sense p• > p• are a predicted result of the plasma depletion and field compression, and such anisotropies are observed. Application of the mirror instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(69 citation statements)
references
References 14 publications
5
64
0
Order By: Relevance
“…The latter serves as a further characterization of the layer, in addition to the f and x behaviour. Observational evidence for the PDL was ®rst reported by Paschmann et al (1978) and Crooker et al (1979). It has subsequently often been observed, and its properties studied, by AMPTE experimenters (Anderson et al, 1991;Paschmann et al, 1993;Phan et al, 1994;Phan and Paschmann, 1995).…”
Section: Introductionmentioning
confidence: 88%
“…The latter serves as a further characterization of the layer, in addition to the f and x behaviour. Observational evidence for the PDL was ®rst reported by Paschmann et al (1978) and Crooker et al (1979). It has subsequently often been observed, and its properties studied, by AMPTE experimenters (Anderson et al, 1991;Paschmann et al, 1993;Phan et al, 1994;Phan and Paschmann, 1995).…”
Section: Introductionmentioning
confidence: 88%
“…As ions can be heated in the perpendicular direction by the quasi-perpendicular bow shock , mirror mode structures are observed in the corresponding terrestrial magnetosheath (Kaufmann et al, 1970;Crooker et al, 1979;Tsurutani et al, 1982) and in the terrestrial cusp (Shi et al, 2009a). Observations and numerical simulations have shown that magnetic peaks are rarely seen in mirror stable plasma because of their rapid decay, but magnetic holes could survive in a mirror stable plasma.…”
Section: Introductionmentioning
confidence: 99%
“…This results in perpendicular compression of the field, a depletion of the total plasma density, and a temperature anisotropy ¹ , '¹ # (Crooker et al, 1979;Anderson and Fuselier, 1993;Zwan and Wolf, 1976). Thus the temperature anisotropy in this ''plasma depletion layer'' can drive Alfve´n/ion-cyclotron or mirror instabilities.…”
Section: The Magnetopause Itselfmentioning
confidence: 99%